Os moinhos de vento de Gustave Flaubert: os efeitos psicanalíticos da relação entre o escritor e a fantasia - Valladares, Tatiana Furquim do Prado (2024)
Writers materialize their fantasies in literary creations, condensing and deforming their experiences, just like in dreams. In this work, we cover the biography of Gustave Flaubert, from his childhood to his literary consecration, psychoanalytically analyzing the consequences arising from the psychic conflict between reality and fantasy suffered by the writer, from his difficulties in adhering to linguistic signs in childhood until the formation of neuroses. The profusion of correspondence and first-person texts produced by Gustave Flaubert throughout his life served as a preliminary source for the development of the psychoanalytic hypotheses presented here. Gustave Flaubert's complex psychic structure challenges psychoanalysts to question to what extent the intensity of the writer's fantasy can be useful for literary production and at what point the predominance of the imaginary can result in psychopathological disorders